Pelatihan Kerajinan Kreatif Sebagai Upaya Penguatan Nilai-Nilai Pancasila Pada Masyarakat Desa Wonosari Kecamatan Bawang Kabupaten Bata - Fiyanto, Arif; Solehudin, Rochmat; Fauni, Ilma Yang; Adiantomo, Yulius Tino; Putri, Marlinda Setya (Universitas Negeri Semarang, 2025)
Togetherness in community life is a very important thing to do. In addition to being able to create a sense of mutual respect and care for others, togetherness is also an implementation of the values of Pancasila which are the basis and philosophy of life of the Indonesian people. Various ways can be done to create a sense or atmosphere of togetherness. Training activities and making creative crafts are one example. The purpose of holding this activity is as an effort to strengthen the values of Pancasila for the people of Wonosari Village, Bawang District, Batang Regency. The method used in implementing this service is in the form of training and mentoring. Creative crafts that are used as training materials are knitting key chains, sewing tote bags, and dyeing fabrics using tie and dye techniques or commonly known as